Primary resistance to integrase strand-transfer inhibitors in Europe. - Casadellà, M; van Ham, P M; Noguera-Julian, M; van Kessel, A; Pou, C; Hofstra, L M; Santos, J R; Garcia, F; Struck, D; Alexiev, I; Bakken Kran, A M; Hoepelman, A I; et al. (J Antimicrob Chemother, 2015)
OBJECTIVES: The objective of this study was to define the natural genotypic variation of the HIV-1 integrase gene across Europe for epidemiological surveillance of integrase strand-transfer inhibitor (InSTI) resistance. METHODS: This was a multicentre, cross-sectional study within the European SPREAD HIV resistance surveillance programme. A representative set of 300 samples was selected from 1950 naive HIV-positive subjects newly diagnosed in 2006-07. The prevalence of InSTI resistance was evaluated using quality-controlled baseline population sequencing of integrase. Signature raltegravir, elvitegravir and dolutegravir resistance mutations were defined according to the IAS-USA 2014 list. In addition, all integrase substitutions relative to HXB2 were identified, including those with a Stanford HIVdb score ≥ 10 to at least one InSTI. To rule out circulation of minority InSTI-resistant HIV, 65 samples were selected for 454 integrase sequencing. RESULTS: For the population sequencing analysis, 278 samples were retrieved and successfully analysed. No signature resistance mutations to any of the InSTIs were detected. Eleven (4%) subjects had mutations at resistance-associated positions with an HIVdb score ≥ 10. Of the 56 samples successfully analysed with 454 sequencing, no InSTI signature mutations were detected, whereas integrase substitutions with an HIVdb score ≥ 10 were found in 8 (14.3%) individuals. CONCLUSIONS: No signature InSTI-resistant variants were circulating in Europe before the introduction of InSTIs. However, polymorphisms contributing to InSTI resistance were not rare. As InSTI use becomes more widespread, continuous surveillance of primary InSTI resistance is warranted. These data will be key to modelling the kinetics of InSTI resistance transmission in Europe in the coming years.
Keywords: Antiretroviral Therapy, Highly Active; CD4 Lymphocyte Count; Cross-Sectional Studies; Drug Resistance, Viral; Europe; Female; Genetic Variation; Genotype; HIV Infections; HIV Integrase; HIV Integrase Inhibitors; HIV-1; Humans; Male; Population Surveillance; Risk Factors; Sequence Analysis, DNA; Viral Load